Development of Android Multimedia “TRIGO-MEDIA” Using AIR Learning Model to Improve Mathematical Problem-Solving Ability - Gunawan Gunawan; Aprilia Nurul Chasanah; Syita Fatih 'Adna (Universitas Sarjanawiyata Tamansiswa, 2022)
This study aims to determine the validity, practicality, and effectiveness of the development of the android multimedia